Ultrasensitive and selective hydrogen sensing of SnO2 nanofibers decorated with Pd single atoms - Xiang, Tao; Yi, Jianxin (Sensors and actuators. B, Chemical, 2024)
Highly accurate and sensitive hydrogen detection particularly at (sub)ppb level is crucial for large-scale use of green hydrogen energy. However, state-of-the-art hydrogen sensors usually have a ppm-level limit of detection (LOD). In this work, SnO2 nanofibers were decorated with Pd single atoms using a scalable two-step annealing method, which remarkably boosted the H2 sensing properties. The Pd-SnO2 nanofiber sensor exhibited a response of 224 to 1000 ppm H2 at the optimum operation temperature of 300°C, which was 107 times higher than that of SnO2, achieving an LOD as low as 0.6 ppb. Moreover, a fast response time of 8.4 s, excellent selectivity, and humidity tolerance were observed. The superior H2 sensing performance of Pd-SnO2 nanofiber was ascribed to excellent catalysis of Pd single atoms and formation of heterojunction. •SnO2 nanofibers decorated with Pd single atoms were fabricated.•Pd-SnO2 exhibited 107-fold higher response to 1000 ppm H2 at 300 °C than SnO2.•A limit of detection down to 0.6 ppb H2 was obtained.•Superior performance was ascribed to Pd catalysis and heterojunction formation.